Socialism in Bessie Head’s “The Prisoner Who Wore Glasses”: A Marxist Reading - Asshary, F. Sandro (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Authors frequently highlight solidarity in literary works, particularly in short stories, to increase the readers’ understanding of the unbalanced economic progress experienced by a certain social class. This attempt happens because they try to create an idealistic society for the working class. From this premise, solidarity was born due to the inability of capitalism to undo the oppression of the working class throughout the decades. Adjusting to capitalist society, the working class is often unconsciously or consciously mistreated to be seen as equal to the upper class. Since socialism is perfectly captured in Bessie Head’s “The Prisoner Who Wore Glasses,” this research aims to analyze the solidarity of the Span One group portrayed in the short story by using Mason’s solidarity, Roskin’s social democracy theories, and Uwe’s qualitative descriptive method. The researcher confirms that the Span One group is portrayed as socialists through their solidarity and social democracy in “The Prisoner Who Wore Glasses” short story. These ideas can be seen through Brille and Span One group’s actions and dialogs.